Pengaruh Belajar Daring pada Masa Pandemi Covid-19 Terhadap Kelolosan Seleksi Kompetensi Dasar Rekrutmen CPNS 2021: - Karimah Opralia, Husnun; Paputungan, Irving Vitra; Dirgahayu, Raden Teduh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The digital platform is used as an online learning tool and as a medium for providing guidance services. Online tutoring services using digital platforms are not only provided for a fee, providers also provide services for free. Functionally, the utilization of these two services is not much different. Online learning methods and use of platforms were utilized in the 2021 CPNS recruitment which was carried out during the COVID-19 pandemic. Thorough preparation must be made to face the Basic Competency Selection. SKD is one of the early stages of CPNS selection which has many competitors and fierce competition not only to meet grades passing grade to pass to the next stage but also must have a high score. Learning online with the use of digital platforms from each participant has a different experience. Through a survey that was distributed online, researchers collected 497 data and took a sample of 400 data from 200 participants who passed and 200 participants who did not pass the passing grade. The data was collected to find out how the influence of online learning carried out by participants on passing the SKD passing grade. This study uses descriptive statistical analysis methods and multiple correspondence analysis. From this analysis, based on the data mapping, it was found that there was an effect of learning methods using digital platforms on the participants' passing. Learning method with independent online learning duration of 4 hours/day, paid online tutoring duration of 2 hours/day, following 2 paid online tutoring services, taking online quizzes practice every day, always actively participating in virtual classes, always listening and discussing discussions materials and quizzes, as well as the ease of accessing materials, quiz exercises, face-to-face learning on digital platforms provided by guidance service providers also affect the passing grade of participants. online learning, digital platforms, technology, utilization, tutoring, passing, passing grades, cpns